2016
DOI: 10.1007/s00415-016-8189-x
|View full text |Cite
|
Sign up to set email alerts
|

Transient monocular blindness and the risk of vascular complications according to subtype: a prospective cohort study

Abstract: Patients with transient monocular blindness (TMB) can present with many different symptoms, and diagnosis is usually based on the history alone. In this study, we assessed the risk of vascular complications according to different characteristics of TMB. We prospectively studied 341 consecutive patients with TMB. All patients were interviewed by a single investigator with a standardized questionnaire; reported symptoms were classified into predefined categories. We performed Cox regression analyses with adjustm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 30 publications
1
15
3
Order By: Relevance
“…Modifiable risk factors such as HTN (52%), hypercholesterolaemia (36%), diabetes (15%) and current smoking (12%) were common in these patients. Our findings add to the results of previously described cohorts of both PVL and TVL, reaffirming the high incidence of risk factors among patients with ischaemic visual loss [9-14]. Similarly, for other forms of cerebrovascular disease, presentation with ischaemic visual loss is an opportunity for secondary prevention and optimisation of modifiable risk factors.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Modifiable risk factors such as HTN (52%), hypercholesterolaemia (36%), diabetes (15%) and current smoking (12%) were common in these patients. Our findings add to the results of previously described cohorts of both PVL and TVL, reaffirming the high incidence of risk factors among patients with ischaemic visual loss [9-14]. Similarly, for other forms of cerebrovascular disease, presentation with ischaemic visual loss is an opportunity for secondary prevention and optimisation of modifiable risk factors.…”
Section: Discussionsupporting
confidence: 73%
“…This recurrence rate is likely to be an underestimate, both due to the lack of prospective follow up and the nature of the population and organisation of services in central London; some patients were only visiting the area and could have had a further event out of region, which we may not have captured. Previous studies showed that long-term recurrence of stroke or retinal occlusion was higher in patients with diabetes, smokers, presentation with more than 3 attacks, and those with significant CAS [9-14, 18]. In contrast, we did not find any factors affecting 90-day recurrence in our cohort, perhaps due to low numbers.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Alternatively, new-onset transient vision loss may be an early sign of a sight-threatening, and possibly life-threatening, emergency. 2,3 This review aims to guide initial management and suggest referral pathways in both of these situations.…”
Section: Discussionmentioning
confidence: 99%
“…The most common cause of monocular transient vision loss is amaurosis fugax, usually resulting from an embolic complication of an ulcerated plaque of the carotid artery. 2 In contrast, the most common cause of transient binocular vision loss is migraine. 4 It is crucial that a thorough history-taking includes an attempt at determining whether one or both eyes were affected as well as discovering the speed of onset, any precipitating factors, the speed of recovery and the presence of any residual symptoms.…”
Section: Discussionmentioning
confidence: 99%